(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2022)
This paper is a tribute to the life and work of Ricard Pearce. The paper discusses some of his key work and makes links with the themes of radical existentialism including navigating the political, racism, ethics, and awareness.